Mitigating the Kinetic Hindrance of Single‐Crystalline Ni‐Rich Cathode via Surface Gradient Penetration of Tantalum - Zou, Yu‐Gang; Mao, Huican; Meng, Xin‐Hai; Du, Ya‐Hao; Sheng, Hang; Yu, Xiqian; Shi, Ji‐Lei; Guo, Yu‐Guo (Angewandte Chemie International Edition, 2021)
Single‐crystalline Ni‐rich cathodes are promising candidates for the next‐generation high‐energy Li‐ion batteries. However, they still suffer from poor rate capability and low specific capacity due to the severe kinetic hindrance at the nondilute state during Li+ intercalation. Herein, combining experiments with density functional theory (DFT) calculations, we demonstrate that this obstacle can be tackled by regulating the oxidation state of nickel via injecting high‐valence foreign Ta5+. The as‐obtained single‐crystalline LiNi0.8Co0.1Mn0.1O2 delivers a high specific capacity (211.2 mAh g−1 at 0.1 C), high initial Coulombic efficiency (93.8 %), excellent rate capability (157 mAh g−1 at 4 C), and good durability (90.4 % after 100 cycles under 0.5 C). This work provides a strategy to mitigate the Li+ kinetic hindrance of the appealing single‐crystalline Ni‐rich cathodes and will inspire peers to conduct an intensive study. The Ta doping created some low‐valence Ni, decreasing the electrostatic repulsion between transition metal and Li+, thus the Li+ diffusion energy barrier has been decreased and the kinetic hindrance was mitigated.